Induced Wide Nematic Phase by Seven-Ring Supramolecular H-Bonded Systems: Experimental and Computational Evaluation - Abdullah Alshabanah, Latifah (Molecules, 2020)
New seven-ring systems of dipyridine derivative liquid crystalline 2:1 supramolecular H-bonded complexes were formed between 4-n-alkoxyphenylazo benzoic acids and 4-(2-(pyridin-4-yl)diazenyl)phenyl nicotinate. Mesomorphic behaviors of the prepared complexes were investigated using a combination of differential scanning calorimetry (DSC) and polarizing optical microscopy (POM). Fermi bands attributed to the presence of intermolecular H-bond interactions were confirmed by FT–IR spectroscopy. All prepared complexes possessed an enantiotropic nematic phase with a broad temperature nematogenic range. Phases were confirmed by miscibility with a standard nematic (N) compound. A comparison was constructed to investigate the influence of the incorporation of the azophenyl moiety on the mesomeric behavior of corresponding five-membered complexes. It was found that the present complexes observed induced a wide nematic phase with relatively higher temperature ranges than the five aromatic systems. Density functional theory (DFT) suggested the nonlinear geometry of the formed complex. The results of the DFT explained the nematic mesophase formation. Moreover, the π–π stacking of the aromatic moiety in the phenylazo acid plays an effective role in the mesomorphic thermal stability. The energy difference between the frontier molecular orbitals, HOMO (highest occupied) and LUMO (lowest occupied), and the molecular electrostatic potential (MEP) of the prepared complexes were estimated by DFT calculations. The results were used to illustrate the observed nematic phase for all H-bonded supramolecular complexes. Finally, photophysical studies were discussed which were carried out by UV spectroscopy connected to a hot stage.